Assessment of Awareness and Knowledge of Food-Drug Interactions Among Medical Students from Different Faculties at Benghazi University, Libya: A Cross-Sectional Comparative Study - Salima Elfagi; Faiza Nouh; Mohamed H Buzgeia; Aya Guma; Doaa Abdel Aziz; Narjes Alsharif; Esraa Abdel Baset (Libyan Journal of Medical and Applied Sciences, 2025)
Food and drug interactions can greatly affect the effectiveness of the drug and its mode of action and may lead to reduced drug effectiveness or serious and fatal side effects, which affects the patient’s condition Evaluate the knowledge and awareness of medical students in medical colleges in the final and pre-final year. A descriptive cross-sectional study was conducted in 2025 ، The study included 771 students from Benghazi Medical University in the final years of the faculties (Medicine, Nutrition, Pharmacy and Dentistry) to assess knowledge, face-to-face interviews were conducted, and the data were statistically analyzed using SPSS. Most of the participants were above the age of 23 years and (75.9%) were female, and the highest percentage (47.3%) were humanities students, followed by dental (21.19%), pharmacy (17.8%) and nutrition (13.7%), of whom (38.1%) were in the penultimate year and (61.9%) in the last year. The results showed a disparity and difference in knowledge between medical specialties, where pharmacy students excelled, followed by medicine, nutrition, and dentistry, due to the pharmacy curriculum’s focus on better interactions, as well as the greater awareness of final year students due to their more experience and greater reliance on self-effort. The study found a significant disparity in knowledge among medical students, where final year students and pharmacy students were more knowledgeable about this topic, and these results reflect the need to focus on curricula and workshops to raise the level.